2019
DOI: 10.2217/imt-2018-0107
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Checkpoint Inhibitors for Wild-Type Advanced Non-Small-Cell Cancer: A Pair-Wise And Network Meta-Analysis

Abstract: Aim: To estimate efficacy of checkpoint inhibitors and rank treatment effects in non-small-cell lung cancer. Materials & methods: Prospective randomized trials were included. p-score was used to rank treatment effects. Results: A total of nine trials were identified, involving 5504 patients and three checkpoint inhibitors. Pembrolizumab plus chemotherapy had the highest p-score of 0.95 among all the treatments, and was superior to pembrolizumab alone (hazard ratio: 0.87; 95% CI: 0.79–0.95). Combination the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Despite these strengths, there have been several controversies. Three studies associated with NMA had been conducted to figure out the best PD-1/L1 inhibitor for advanced NSCLC patients in the first-line settings (51)(52)(53). Our results were generally consistent with the previous studies, which had all indicated the combination of pembrolizumab to be better than other combined therapies or chemotherapies for patients with relatively high expression of PD-L1.…”
Section: Discussionsupporting
confidence: 89%
“…Despite these strengths, there have been several controversies. Three studies associated with NMA had been conducted to figure out the best PD-1/L1 inhibitor for advanced NSCLC patients in the first-line settings (51)(52)(53). Our results were generally consistent with the previous studies, which had all indicated the combination of pembrolizumab to be better than other combined therapies or chemotherapies for patients with relatively high expression of PD-L1.…”
Section: Discussionsupporting
confidence: 89%
“…Wang et al (63) confirmed that 1st line immunotherapy, either nivolumab, pembrolizumab or atezolizumab considering monotherapy or combined chemo-immunotherapy, had better efficacy than chemotherapy in reducing disease progression (HR 0.69, 95% CI 0.56-0.86; p = 0.001) and mortality (HR 0.74, 95% CI 0.63-0.87; p < 0.001), and that grade 3-5 adverse events were less pronounced with immunotherapy monotherapy (RR 0.42, 95% CI 0.35-0.51; p < 0.001) but were worse with combined chemo-immunotherapy (RR 1.15, 95% CI 1.04-1.27; p = 0.008). Using pembrolizumab alone (P-score 0.65) as the reference comparator, only pembrolizumab plus platinum doublet (HR 0.87, 95% CI 0.79-0.95; P-score 0.95) showed any significant superiority while combination including nivolumab or atezolizumab did not (HR 0.93-1.13).…”
Section: Which Is the Best Treatment Duration?mentioning
confidence: 99%
“…One issue deserved attention for the patients with lower-level, negative, or unknown PD-L1 status: whether they should be excluding the possible benefit from ICIs. A subgroup analysis in a meta-analysis showed that patients with PD-L1 expression of <1% also derived benefit from ICIs ( 50 ). Furthermore, PD-L1 status has low sensibility (72%) and specificity (58%), thus PD-L1 status alone is not an appropriate biomarker to optimize immunotherapy.…”
Section: Discussionmentioning
confidence: 99%